Designing A Disaster Preparedness Bag by Considering Ergonomics Aspect - Patrisina, Reinny; Hadiguna, Rika Ampuh; Taufik, Taufik; Muluk, Asmuliardi; Putra, Havis Dwi (CIVED, 2024)
Disasters may make people having to evacuate. When evacuating, evacuee may bring items required in evacuation place. The items must be ready previously in a bag, called a disaster preparedness bag. In case a disaster occurs, evacuee just grabs it and go for evacuation. Many bags used are not dedicated for disaster situation. Many types of items stored together and mixed causing of difficulty in retrieval. In addition, use of inappropriate bag will interfere with evacuee movement and slow down the evacuee while the evacuation time is too short. This research aims to design ergonomics disaster preparedness bag that can accommodate needs for 3x24 hours. Design process was started with planning phase to find out disaster preparedness bag development opportunity. The second phase is concept development. People who have evacuation experience are asked report their complaints regarding the bag used during previous evacuation and their needs for a disaster preparedness bag. Based on the needs, target specification is determined then concept alternatives are generated and selected. Then, main parts of the bag are identified. Continued with detailed design process, the dimensions of the proposed bag are determined using anthropometric data and dimension of required item in the first 72 hours of evacuation time. The design of proposed bag is such a backpack with multi compartments adjusted to item stored. The shoulder straps are designed like a vest then the load is not focused only on the shoulder but distributed to other part of body such as abdominal and chest muscle.